Implications of the School Literacy Movement with Picture Storybook Media - Zunidar Zunidar (Universitas Pahlawan Tuanku Tambusai, 2022)
Interest and reading power are latent problems that occur in students and educators. On this basis, a government policy was issued in Permendikbud Number 23 of 2015 concerning the School Literacy Movement (GLS). One of the mandatory efforts is reading 15 minutes of non-lesson books every day (story books or other books). This study aims to analyze the implications of the school literacy movement using picture story books as media. The type of this research is qualitative with literature study method. The research materials and analysis studies are obtained through scientific reference sources, including books, articles, proceedings, theses, theses, and dissertations. These scientific sources are obtained through credible sites, such as Google Scholar, DOAJ, and SINTA. The results of this study indicate that the activities of the school literacy movement through the media of picture story books have a significant impact on students' reading power and interest. This is in terms of increasing students' knowledge insight, motivation to read books in students, and forming active literacy characters in students. The GLS stages include 15 minutes of reading pre-learning picture story books, reading prayers, reading verses of the Koran in short suras, singing the national anthem, and strengthening the teacher for the previous meeting's teaching materials. Thus, students are increasingly moving to get used to and love the world of literacy